Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008 International Symposium on Information Technology 2008
DOI: 10.1109/itsim.2008.4631946
|View full text |Cite
|
Sign up to set email alerts
|

Efficient forward and reverse converters for a new high-radix moduli set

Abstract: The residue number system (RNS) is a carry-free number system which can support parallel and highspeed arithmetic. In this paper, efficient and simple designs of forward and reverse converters for the new radix-r moduli set {r 2n , r n -1} are presented. This moduli set contains well-formed moduli which can result in fast RNS arithmetic and efficient forward and reverse conversion. In comparison with the last work, the proposed designs achieve higher-speed and lowercost resulting in higher overall performance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
0
0
Order By: Relevance
“…The arithmetic unit of the residue number system includes the modular adder, multiplier, and subtractor for each modulus channel [31][32]. The residue numbers are converted to their weighted equivalents in the binary system by a reverse converter to utilize the outcomes of arithmetic operations [33][34]. Reverse converter algorithms are basically based on the mixed-radix conversion (MRC) [35], Chinese remainder theorem (CRT) [36][37], new Chinese remainder-1 [38][39], and new Chinese remainder-2 [40].…”
Section: Rns Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…The arithmetic unit of the residue number system includes the modular adder, multiplier, and subtractor for each modulus channel [31][32]. The residue numbers are converted to their weighted equivalents in the binary system by a reverse converter to utilize the outcomes of arithmetic operations [33][34]. Reverse converter algorithms are basically based on the mixed-radix conversion (MRC) [35], Chinese remainder theorem (CRT) [36][37], new Chinese remainder-1 [38][39], and new Chinese remainder-2 [40].…”
Section: Rns Backgroundmentioning
confidence: 99%
“…The computation of α has been debated in [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43]. It is shown that selecting suitable constants q,  and performing boundary condition of Eq.…”
Section: Sum Of Residues Reduction Backgroundmentioning
confidence: 99%